The Impact of Using Podcasting and Video casting on improving Eighth Graders’ Communication Skills in English Language - Wissam Abu Shunnar; Bashar Abu Shunnar (Britain International for Academic Research (BIAR) Publisher, 2022)
The study aimed to investigate the impact of using Podcasting and Video casting on improving communication skills for Eighth graders in Madaba Schools. The study was using a quasi-experimental approach, splitting the study sample into three groups: Podcasting (25) students, Video casting (28) students, and the control group (21) students. An oral test scale for students' communication abilities was developed, and its validity and reliability were validated by administering it to a pilot sample of (25) students who were not part of the main sample group. According to the findings, the use of Podcasting and Video casting leads to statistically significant differences in the level of Eighth -grade students' acquisition of communication skills in the English language when compared to their peers in the control group, who were taught in the conventional method. Furthermore, the findings revealed that video casting had a more significant positive influence on enhancing students' communication abilities than podcasting. Finally, several recommendations were made, including the need to activate the use of Podcasting and Video casting in teaching communication skills, as well as the need to re-evaluate current English language curricula to include classroom activities that are in line with the requirements of using Podcasting and Videoc asting in teaching the English language.